Preparation method of ultrahigh corrosion-resistant coating of magnesium alloy

By directly electroplating aluminum after electrodeposition of zinc on the surface of the magnesium alloy, combined with ionic liquid preparation and sandblasting anodization treatment, the problems of poor corrosion resistance of magnesium alloy and insufficient binding force are solved, and efficient and low-cost coating preparation is achieved, suitable for AZ31B and AZ91D magnesium alloys.

CN120366862APending Publication Date: 2025-07-25交叉离子(杭州)新材料科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510438055.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-09
Publication Date
2025-07-25

AI Technical Summary

Technical Problem

The corrosion resistance of magnesium alloys is poor, the existing plating layer has insufficient bonding power to the substrate, and the plating process is complex and costly, making it difficult to deposit a plating layer with excellent bonding power and dense bonding power on the surface of magnesium alloys.

Method used

The method of directly electroplating aluminum after electrodeposition of zinc in magnesium alloy is adopted. The electrodeposition parameters are prepared and controlled by additive-free ionic liquid, combined with sandblasting and anodizing treatment, and ultra-high corrosion-resistant plating is formed.

Benefits of technology

It realizes excellent binding force between the plating and the substrate, has simplified process, high stability and low cost, and is suitable for AZ31B and AZ91D magnesium alloys, with commercial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120366862A_ABST
    Figure CN120366862A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of magnesium alloy surface treatment, and discloses a preparation method of an ultrahigh corrosion-resistant coating of a magnesium alloy, which comprises the following steps: step 1, electrodepositing zinc on the magnesium alloy; step 2, preparing an ionic liquid; 3, the magnesium alloy subjected to zinc electroplating is directly subjected to aluminum electroplating; step 4, cleaning; and step 5, post-processing. After a layer of zinc is electroplated on the surface of the magnesium alloy, aluminum is directly plated, the process is simplified, the stability and controllability are high, the cost is low, and the coating binding force is excellent. And meanwhile, successful deposition can be performed on the two magnesium alloys AZ31B and AZ91D, so that the process is less affected by a base material, and the process has a very good commercial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of surface treatment of magnesium alloys, and particularly relates to a method for preparing a super high corrosion-resistant coating on magnesium alloys. Background Art

[0002] Magnesium alloys have the lowest density among structural metals and their alloy materials, about 1.74 g / cm 3 , which is 2 / 3 of aluminum and 1 / 4 of iron. In addition, magnesium alloys also have a series of advantages, such as: (1) low elastic modulus. (2) Structural metals that are easy to process. (3) Strong thermal and electrical conductivity. (4) Good electromagnetic shielding property, etc. However, magnesium has a very high activity, and the standard hydrogen electrode potential is -2.37 V, with a large thermodynamic corrosion tendency, so it is extremely corrosion-resistant. The poor corrosion resistance of magnesium alloys severely restricts their applications. Therefore, without sacrificing the mechanical properties of magnesium alloys themselves, by means of surface engineering technology, the purpose of anti-corrosion can be achieved and it can have a certain degree of aesthetics.

[0003] The surface treatment of magnesium alloys mainly involves conversion and plating: Although chemical conversion has a strong bond with the substrate, the film layer is thin and soft, and it is usually only used as a coating substrate. Although anodic oxidation and micro-arc oxidation have a good bond with the substrate, and have good insulation, decoration, and wear resistance, the process is complex and unstable, the equipment investment is large, the efficiency is low, and the cost is high. In the plating method, the bonding force between the coating and the substrate is the main difficulty. So far, only zinc and nickel can deposit coatings with excellent bonding force on the surface of magnesium alloys. Considering the influence of galvanic corrosion between the coating and the substrate, zinc coatings are usually selected. There are two ways to deposit zinc coatings: immersion zinc and electroplating zinc. Immersion zinc treatment obtains a thin zinc layer on the surface of magnesium alloys through a displacement reaction, and electroplating zinc obtains a zinc layer with a required thickness on the surface of magnesium alloys through electro-deposition according to the electro-deposition time. The bonding force between the electro-deposited zinc coating and the substrate is jointly affected by the stability of the plating solution, the type of substrate material, and process parameters. It is the biggest difficulty to obtain a coating with excellent bonding force and certain stability. At the same time, on the premise of having a zinc coating with a certain bonding force, it is further difficult to obtain a zinc layer with a certain density and flatness. After plating multiple layers of zinc on magnesium alloys and then plating an aluminum-manganese coating with inorganic molten salt, the process is relatively complex, the electroplating temperature is high, the equipment corrosion is serious, and the operation is dangerous.

[0004] Metallic aluminum (Al) has a low density, high ductility, and a certain luster. In particular, Al can form a uniform and dense passivation film on its surface in a natural environment, having a certain corrosion resistance, and the post-treatment of the aluminized layer is well-developed, such as anodic oxidation process can further improve corrosion resistance and wear resistance. Summary of the Invention

[0005] The purpose of the present invention is to provide a method for preparing a super high corrosion-resistant coating on magnesium alloys to solve the above technical problems.

[0006] To solve the above technical problems, the specific technical solution of a method for preparing a super high corrosion-resistant coating on a magnesium alloy of the present invention is as follows: A method for preparing a super high corrosion-resistant coating on a magnesium alloy, comprising the following steps: Step 1, electro-depositing zinc on the magnesium alloy; Step 2, preparing an ionic liquid; Step 3, directly electroplating aluminum on the electro-galvanized magnesium alloy; Step 4, cleaning; Step 5, post-treatment.

[0007] Furthermore, the said Step 1 comprises the following steps: Step 1.1, substrate preparation: Using two kinds of magnesium alloys, AZ31B or AZ91D, mechanically polished with sandpaper to 800 meshes for standby; Step 1.2, electro-depositing zinc: AZ31B or AZ91D are pretreated with the same process parameters, and then electro-depositing zinc on their surfaces to form a zinc layer on the magnesium alloy surface.

[0008] Furthermore, the said Step 2 comprises the following steps: Step 2.1, preparing an ionic liquid without additives; Step 2.2, preparing an ionic liquid containing additives with bright and smooth effects.

[0009] Furthermore, the said Step 2.1 comprises the following steps: Taking anhydrous AlCl3 and EMIC as raw materials, preparing the liquid in a glove box, such that the molar ratio of AlCl3 to EMIC is 1.5 - 2:1, and controlling the temperature ≤ 60 °C during the liquid preparation.

[0010] Furthermore, the said Step 2.1 comprises the following steps: Adding additives with bright and smooth effects to the ionic liquid prepared in Step 2.1. The additives are 3-pyridinecarboxamide, 4-cyanopyridine, nicotinamide, and o-phenanthroline, with a concentration of 0.01 - 2 g / L. The preparation temperature is room temperature, and it is fully stirred until completely complexed.

[0011] Furthermore, the said Step 3 comprises the following steps: The electro-deposition experiment is carried out under an inert atmosphere condition to ensure that the water and oxygen content ≤ 0.01 ppm; using a high-purity aluminum plate as the anode and the zinc-plated magnesium alloy as the cathode for electro-deposition; an ionic liquid with a molar ratio of AlCl3:EMIC of 1.5 - 2:1, the content of additives with bright and smooth effects is 0.01 - 2 g / L, the electro-deposition current density is 5 - 20 mA / cm 2 , and the electro-deposition temperature is from room temperature to 60 °C.

[0012] Further, step 4 includes the following steps: After the aluminum coating obtained by electrodeposition is taken out of the glove box, it is immediately put into absolute ethanol for cleaning. The cleaning time is 1 - 2 minutes, the cleaning temperature is room temperature, and the number of cleaning times is 2 times. At the same time, it is cleaned with deionized water. The cleaning temperature is room temperature, the cleaning time is 1 - 2 minutes, and the number of cleaning times is 2 times.

[0013] Further, step 5 includes the following steps: Step 5.1, sandblasting: white corundum is used for sandblasting treatment, 0.1 - 0.2 MPa, the time is 1 - 2 minutes, and the number of times is 1 - 2 times, so that the surface of the coating is uniform; Step 5.2, anodic oxidation: oxidized in sulfuric acid solution, the concentration is 180 - 200 g / L, the aluminum ion concentration is 0 - 15 g / L, and the current density is 10 - 15 mA / cm 2 , the temperature is 15 - 25 °C, and the time is 25 - 35 minutes; Step 5.3, neutral salt spray test: 5% NaCl aqueous solution, the temperature is 35 °C ± 1 °C, the temperature of the saturated air tank is 35 - 40 °C, the relative humidity is 85%, the spray corrosion collection amount is 1 - 2 ml / 80 cm * 1 h, the temperature of the brine tank is 35 °C ± 1 °C, and the pH value of the brine solution is 6.5 - 7.2.

[0014] The method for preparing a super corrosion-resistant coating for a magnesium alloy of the present invention has the following advantages: The present invention directly electroplates aluminum after electroplating a layer of zinc on the surface of the magnesium alloy: the process is simplified, the stability is high, the controllability is high, the cost is low, and the binding force of the coating is excellent. At the same time, it can be successfully deposited on two kinds of magnesium alloys, AZ31B and AZ91D, so it is less affected by the substrate and is a process with very promising commercial application prospects. Description of the Drawings

[0015] Figure 1 It is the SEM diagram of the anodic oxidation of AZ31B magnesium alloy; Figure 2 It is the SEM diagram of the anodic oxidation of AZ91D magnesium alloy; Figure 3 It is the cross-sectional SEM diagram of the anodic oxidation of the aluminum coating of AZ31B magnesium alloy; Figure 4 It is the cross-sectional SEM diagram of the anodic oxidation of the aluminum coating of AZ91D magnesium alloy; Figure 5 It is the appearance diagram of the anodic oxidation coating of AZ31B magnesium alloy after 2088 h and 2256 h neutral salt spray experiments; Figure 6 It is the appearance diagram of the anodic oxidation coating of AZ91D magnesium alloy after 2088 h and 2256 h neutral salt spray experiments. Detailed Embodiments

[0016] To better understand the purpose, structure, and function of the present invention, the following further describes in detail a method for preparing a super-high corrosion-resistant coating on a magnesium alloy of the present invention with reference to the accompanying drawings.

[0017] A method for preparing a super-high corrosion-resistant coating on a magnesium alloy of the present invention includes the following steps: Step 1: Electro-deposit zinc on the magnesium alloy; Step 1.1: Substrate preparation: Use two types of magnesium alloys, AZ31B or AZ91D, and mechanically polish them with sandpaper to 800 mesh for standby; Step 1.2: Electro-deposit zinc: AZ31B or AZ91D is pretreated with the same process parameters, and then zinc is electro-deposited on its surface to form a zinc layer on the magnesium alloy surface.

[0018] Step 2: Prepare the ionic liquid; Step 2.1: Preparation of the additive-free ionic liquid: Take a certain amount of anhydrous AlCl3 and EMIC as raw materials, and carry out liquid preparation in a glove box (water and oxygen content ≤ 0.01 ppm) so that the molar ratio of AlCl3 to EMIC is 1.5 - 2:1. The temperature during liquid preparation needs to be controlled ≤ 60 °C.

[0019] Step 2.2: Preparation of the ionic liquid containing an additive with a bright and smooth effect: Add an additive with a bright and smooth effect to the ionic liquid prepared in Step 2.1. The additive is 3-pyridinecarboxamide, 4-cyanopyridine, nicotinamide, or o-phenanthroline, and the concentration is 0.01 - 2 g / L. The preparation temperature is room temperature, and it is fully stirred until complete complexation.

[0020] Step 3: Directly conduct an electroplating aluminum experiment on the electro-galvanized magnesium alloy.

[0021] Aluminum plating process parameters: The electro-deposition experiment is carried out under an inert atmosphere condition, that is, it is necessary to ensure that the water and oxygen content ≤ 0.01 ppm. An ionic liquid with a molar ratio of AlCl3:EMIC of 1.5 - 2:1, the content of the additive with a bright and smooth effect is 0.01 - 2 g / L, the electro-deposition current density is 5 - 20 mA / cm 2 , the electro-deposition thickness (depending on the actual required thickness), and the electro-deposition temperature is from room temperature to 60 °C. In the experiment, a high-purity aluminum plate is used as the anode, and the zinc-plated magnesium alloy is used as the cathode for the electro-deposition experiment.

[0022] Step 4: Cleaning: The electro-deposited aluminum coating needs to be taken out from the inert atmosphere. Its surface contains residual ionic liquid. After taking it out of the glove box, it needs to be immediately put into absolute ethanol for cleaning. The cleaning time is 1 - 2 minutes, the cleaning temperature is room temperature, and the cleaning times are 2 times. At the same time, it needs to be cleaned with deionized water. The cleaning temperature is room temperature, the cleaning time is 1 - 2 minutes, and the cleaning times are 2 times.

[0023] Step 5: Post-treatment; Step 5.1, Sandblasting: Carry out sandblasting treatment with white fused alumina, at 0.1 - 0.2 MPa, for 1 - 2 minutes, with 1 - 2 times, to make the surface of the coating uniform.

[0024] Step 5.2, Anodic oxidation: Oxidize in sulfuric acid solution, with a concentration of 180 - 200 g / L, aluminum ion concentration of 0 - 15 g / L, current density of 10 - 15 mA / cm 2 , at a temperature of 15 - 25 °C, for 25 - 35 minutes.

[0025] Step 5.3, Neutral salt spray test: 5% NaCl aqueous solution, at a temperature of 35 °C ± 1 °C, saturated air tank temperature of 35 - 40 °C, relative humidity of 85%, spray corrosion collection amount of 1 - 2 ml / 80 cm * 1 h, brine tank temperature of 35 °C ± 1 °C, brine solution pH value of 6.5 - 7.2.

[0026] Example 1 1. Mechanical polishing: Polish AZ31B and AZ91D magnesium alloys successively with 600 - mesh and 800 - mesh sandpapers.

[0027] 2. Degreasing: Carry out degreasing treatment by ultrasonic cleaning with absolute ethanol at room temperature for 15 minutes.

[0028] 3. Electro - deposit zinc.

[0029] 4. Deionized water cleaning: Carry out two - pass deionized water cleaning, with each room - temperature rinsing for 15 s, to remove the residual zinc solution.

[0030] 5. Absolute ethanol cleaning: Rinse with absolute ethanol at room temperature for 15 s, and dry for standby.

[0031] 6. Electro - plate aluminum coating: The molar ratio of AlCl3 and EMIC is 2:1, with an additive containing bright and flat effect of 0.1 g / L, current density of 10 mA / cm 2 , electro - deposition time of 120 minutes, electro - deposition temperature of 35 °C. In the experiment, a high - purity aluminum plate is used as the anode, and the zinc - plated magnesium alloy is used as the cathode for electro - deposition experiments.

[0032] 7. Cleaning: Ultrasonic cleaning with absolute ethanol for 2 minutes, cleaning temperature at room temperature, cleaning times 2 times. Ultrasonic cleaning with deionized water, cleaning temperature at room temperature, cleaning time 2 minutes, cleaning times 2 times.

[0033] 8. Sandblasting: White fused alumina, pressure 0.1 MPa, time 1 minute, number of times 1 time, until the surface is overall uniform.

[0034] 9. Anodic oxidation: Oxidize in sulfuric acid solution, with a concentration of 190 g / L, aluminum ion concentration of 0.3 g / L, current density of 15 mA / cm 2, Temperature: 18°C, Time: 35 min. Sealing hole temperature: 65°C, Sealing hole time: 10 min.

[0035] 10. Neutral salt spray test: 5% NaCl aqueous solution, temperature 35°C ± 1°C, saturated air tank temperature 35°C, relative humidity 85%, spray corrosion collection volume 1 ml / 80 cm²·h, brine tank temperature 35°C, brine solution pH value 6.5. Samples after 2256 h of neutral salt spray test did not show obvious corrosion.

[0036] Example 2 1. Mechanical grinding: AZ31B and AZ91D magnesium alloys were ground successively with 600-mesh and 800-mesh sandpapers.

[0037] 2. Degreasing: Degreasing treatment was carried out by ultrasonic cleaning with absolute ethanol at room temperature for 15 min.

[0038] 3. Electroplating zinc.

[0039] 4. Deionized water cleaning: Two-pass deionized water cleaning was adopted, with each room temperature rinsing for 15 s to remove the residual zinc solution.

[0040] 5. Absolute ethanol cleaning: Rinsing with absolute ethanol at room temperature for 15 s, then drying for standby.

[0041] 6. Electroplating aluminum coating: The molar ratio of AlCl3 to EMIC is 1.5:1, additive 0.5 g / L, current density 15 mA / cm² 2 , Electroplating time 100 min, electroplating temperature 40°C. In the experiment, high-purity aluminum plate was used as the anode and zinc-plated magnesium alloy as the cathode for electroplating experiment.

[0042] 7. Cleaning: Ultrasonic cleaning with absolute ethanol for 2 min, cleaning temperature at room temperature, cleaning times 2 times. Ultrasonic cleaning with deionized water, cleaning temperature at room temperature, cleaning time 2 min, cleaning times 2 times.

[0043] 8. Sandblasting: White fused alumina, pressure 0.2 MPa, time 2 min, number of times 1 time, until the surface is uniformly consistent.

[0044] 9. Anodic oxidation: Oxidation in sulfuric acid solution, concentration 180 g / L, aluminum ion concentration 10 g / L, current density 10 mA / cm² 2 , Temperature 25°C, time 25 min. Sealing hole temperature 65°C, sealing hole time 10 min.

[0045] 10. Neutral salt spray test: 5% NaCl aqueous solution, temperature 36 °C, saturated air tank temperature 40 °C, relative humidity 85%, spray corrosion collection volume 2 ml / 80 cm * 1 h, brine tank temperature 34 °C, brine solution pH value 7.2. Samples after 2256 h of neutral salt spray test did not show obvious corrosion.

[0046] Experimental results: Figure 1 Figure 2 is the surface microtopography diagram after anodizing electroplated aluminum on magnesium alloy. The coating is flat, dense and has no obvious microcracks; Figure 3 Figure 4 is the cross-section diagram after anodizing electroplated aluminum on magnesium alloy. The bonding between each coating is good and there is no potential microcrack; Figure 5 Figure 6 is the appearance diagram of the magnesium alloy anodized aluminum coating after neutral salt spray test. The coating surface of the specimen after 2256 h of neutral salt spray test has no obvious corrosion and the corrosion resistance is very excellent.

[0047] It can be understood that the present invention is described by some embodiments. Those skilled in the art know that without departing from the spirit and scope of the present invention, various changes or equivalent replacements can be made to these features and embodiments. In addition, under the teaching of the present invention, these features and embodiments can be modified to adapt to specific situations and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application belong to the scope protected by the present invention.

Claims

1. A method for preparing an ultra-high corrosion-resistant coating on a magnesium alloy, characterized in that, It includes the following steps: Step 1: Electro-deposit zinc on the magnesium alloy; Step 2: Prepare the ionic liquid; Step 3: Directly electroplate aluminum on the electro-galvanized magnesium alloy; Step 4: Clean; Step 5: Post-treatment.

2. The method for preparing a super corrosion-resistant coating on a magnesium alloy according to claim 1, characterized in that, The said Step 1 includes the following steps: Step 1.1: Substrate preparation: Use two kinds of magnesium alloys, AZ31B or AZ91D, and mechanically polish them with sandpaper to 800 meshes for standby; Step 1.2: Electro-deposit zinc: Pretreat AZ31B or AZ91D with the same process parameters, and then electro-deposit zinc on its surface to form a zinc layer on the surface of the magnesium alloy.

3. The method for preparing an ultra-high corrosion-resistant coating on a magnesium alloy according to claim 1, characterized in that, The said Step 2 includes the following steps: Step 2.1: Prepare the additive-free ionic liquid; Step 2.2: Prepare the ionic liquid containing additives with bright and smooth effects.

4. The method for preparing a super corrosion-resistant coating on a magnesium alloy according to claim 3, characterized in that, The said Step 2.1 includes the following steps: Take anhydrous AlCl3 and EMIC as raw materials, and carry out liquid preparation in a glove box, so that the molar ratio of AlCl3 to EMIC is 1.5 - 2:1, and control the temperature ≤ 60 °C during liquid preparation.

5. The method for preparing an ultra-high corrosion-resistant coating on a magnesium alloy according to claim 3, characterized in that, The said Step 2.1 includes the following steps: Add additives with bright and smooth effects to the ionic liquid prepared in Step 2.

1. The additives are 3-pyridinecarboxamide, 4-cyanopyridine, nicotinamide, and o-phenanthroline, and the concentration is 0.01 - 2 g / L. The preparation temperature is room temperature, and stir fully until complete complexation.

6. The method for preparing a super corrosion-resistant coating on a magnesium alloy according to claim 1, characterized in that, The said Step 3 includes the following steps: The electrodeposition experiment was carried out under an inert atmosphere condition to ensure that the water and oxygen content ≤ 0.01 ppm; a high-purity aluminum plate was used as the anode, and a galvanized magnesium alloy was used as the cathode for electrodeposition; an ionic liquid with an AlCl3:EMIC molar ratio of 1.5 - 2:1, the additive content for a bright and flat effect was 0.01 - 2 g / L, and the electrodeposition current density was 5 - 20 mA / cm 2 , and the electrodeposition temperature was from room temperature to 60 °C.

7. The method for preparing a super corrosion-resistant coating on a magnesium alloy according to claim 1, characterized in that, The said Step 4 includes the following steps: After taking out the electro-deposited aluminum coating from the glove box, immediately put it into absolute ethanol for cleaning. The cleaning time is 1 - 2 min, the cleaning temperature is room temperature, the cleaning times are 2 times. At the same time, clean it with deionized water. The cleaning temperature is room temperature, the cleaning time is 1 - 2 min, and the cleaning times are 2 times.

8. The method for preparing a super corrosion-resistant coating on a magnesium alloy according to claim 1, characterized in that, The said Step 5 includes the following steps: Step 5.1: Sandblasting: Carry out sandblasting treatment with white corundum, 0.1 - 0.2 MPa, time 1 - 2 min, times 1 - 2 times, to make the surface of the coating uniform; Step 5.2, Anodic oxidation: Oxidation in sulfuric acid solution with a concentration of 180 - 200 g / L, aluminum ion concentration of 0 - 15 g / L, current density of 10 - 15 mA / cm 2 , temperature of 15 - 25 °C, and time of 25 - 35 min; Step 5.3: Neutral salt spray test: 5% NaCl aqueous solution, temperature 35 °C ± 1 °C, saturated air tank temperature 35 - 40 °C, relative humidity 85%, spray corrosion collection amount 1 - 2 ml / 80 cm * 1 h, brine tank temperature 35 °C ± 1 °C, brine solution pH value 6.5 - 7.2.